2017
DOI: 10.3389/fneur.2017.00006
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Activation of Invariant Natural Killer T Cells and TH2-Skewed Immunity in Stroke Patients

Abstract: BackgroundInfection is highly prevalent and contribute significantly to mortality of stroke patients. In addition to the well described robust systemic lymphocytopenia and skewed T helper 2 (TH2)-immunity after stroke, emerging experimental evidence demonstrate that the development of infection poststroke is attributed by the activation of invariant natural killer T (iNKT) cells. In this prospective study, we examined the levels of a broad spectrum of inflammatory mediators, the activation status of iNKT cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…We found that patients with complete (TICI 3) recanalization after the thrombectomy had less severe impairments in their autoregulation than patients with incomplete recanalization (TICI 2a or 2b). Impairments in autoregulation were primarily observed 24 to 96 h after the LSW time and were bilateral, affecting both the ipsilateral and contralateral hemispheres, supporting prior work demonstrating the presence of global impairments in autoregulation after an ischemic stroke [ 10 , 13 , 37 ]. However, some prior studies have demonstrated the presence of unilateral impairments in cerebral autoregulation [ 12 , 38 , 39 ], suggesting an element of interpatient variability, with some suggesting that large-vessel atherosclerosis and small-vessel disease likely contribute to bilateral impairments [ 37 , 39 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We found that patients with complete (TICI 3) recanalization after the thrombectomy had less severe impairments in their autoregulation than patients with incomplete recanalization (TICI 2a or 2b). Impairments in autoregulation were primarily observed 24 to 96 h after the LSW time and were bilateral, affecting both the ipsilateral and contralateral hemispheres, supporting prior work demonstrating the presence of global impairments in autoregulation after an ischemic stroke [ 10 , 13 , 37 ]. However, some prior studies have demonstrated the presence of unilateral impairments in cerebral autoregulation [ 12 , 38 , 39 ], suggesting an element of interpatient variability, with some suggesting that large-vessel atherosclerosis and small-vessel disease likely contribute to bilateral impairments [ 37 , 39 ].…”
Section: Discussionsupporting
confidence: 73%
“…For example, post-stroke impairment in autoregulation has been associated with poor outcomes, including larger infarct volumes and increased rates of hemorrhagic conversion. These impairments are particularly prominent within the first five days post stroke [ 10 , 11 ], and appear to be global, affecting both the ipsilateral and the contralateral hemispheres [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Second, ischemic stroke triggers sustained and stable changes in the systemic immune system, including specific lymphopenia, excessive production of IL-10, and prolonged Th2 biased immunity, all of which lead to severe immunosuppression in stroke patients. [ 24 ] The OX40L-OX40 pathway could enhance Th2 responses, and this indicates that patients with high serum OX40L have high likelihood to develop low immune function and are prone to various infections. [ 25 ] In this article, nonsurvivors of CI patients showed significantly higher rate of pulmonary infection than survivors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the subgroups of T cells that promote neurogenesis were not identified. In fact, there are huge discrepancies with respect to cytokine production from Th1 or Th2 cells and the ratio of Th1/Th2 cells can even affect stroke severity . Th17 cells and γδ T cells produce pro‐inflammatory cytokines and chemokines, usually impairing neurogenesis .…”
Section: The Role Of Neuroinflammation In Multiple Brain Repair Mechamentioning
confidence: 99%